Silencing MicroRNA-134 Alleviates Hippocampal Damage and Occurrence of Spontaneous Seizures After Intraventricular Kainic Acid-Induced Status Epilepticus in Rats - Gao, Xiaoying; Guo, Mian; Meng, Dawei; Sun, Feixiang; Guan, Lianyue; Cui, Ying; Zhao, Yan; Wang, Xichun; Gu, Xin; Sun, Jiahang; Qi, Sihua (Frontiers in Cellular Neuroscience, 2019)
Epilepsy is a disorder of abnormal brain activity typified by spontaneous and recurrent seizures. MicroRNAs (miRNAs) are short noncoding RNAs, critical for the post-transcriptional regulation of gene expression. MiRNA dysregulation has previously been implicated in the induction of epilepsy. In this study, we examined the effect of silencing miR-134 against status epilepticus (SE). Our results showed that level of miR-134 was significantly up-regulated in rat brain after Kainic acid (KA)-induced SE. TUNEL staining showed that silencing miR-134 alleviated seizure-induced neuronal apoptosis in the CA3 subfield of the hippocampus. Western blot showed that a miR-134 antagonist suppressed lesion-induced endoplasmic reticulum (ER) stress and apoptosis related expression of CHOP, Bim and Cytochrome C, while facilitated the expression of CREB at 24 h post KA-induced lesion in the hippocampus. Consistently, silencing miR-134 significantly diminished loss of CA3 pyramidal neurons using Nissl staining as well as reducing aberrant mossy fiber sprouting (MFS) in a rat epileptic model. In addition, the results of EEG and behavior analyses showed seizures were alleviated by miR-134 antagonist in our experimental models. These results suggest that silencing miR-134 modulates the epileptic phenotype by upregulating its target gene, CREB. This in turn attenuates oxidative and ER stress, inhibits apoptosis, and decreases MFS long term. This indicates that silencing miR-134 might be a promising intervention for the treatment of epilepsy.